If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 2) = 2x + -1 + 5(2x + 1) Reorder the terms: -2(2 + x) = 2x + -1 + 5(2x + 1) (2 * -2 + x * -2) = 2x + -1 + 5(2x + 1) (-4 + -2x) = 2x + -1 + 5(2x + 1) Reorder the terms: -4 + -2x = 2x + -1 + 5(1 + 2x) -4 + -2x = 2x + -1 + (1 * 5 + 2x * 5) -4 + -2x = 2x + -1 + (5 + 10x) Reorder the terms: -4 + -2x = -1 + 5 + 2x + 10x Combine like terms: -1 + 5 = 4 -4 + -2x = 4 + 2x + 10x Combine like terms: 2x + 10x = 12x -4 + -2x = 4 + 12x Solving -4 + -2x = 4 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -4 + -2x + -12x = 4 + 12x + -12x Combine like terms: -2x + -12x = -14x -4 + -14x = 4 + 12x + -12x Combine like terms: 12x + -12x = 0 -4 + -14x = 4 + 0 -4 + -14x = 4 Add '4' to each side of the equation. -4 + 4 + -14x = 4 + 4 Combine like terms: -4 + 4 = 0 0 + -14x = 4 + 4 -14x = 4 + 4 Combine like terms: 4 + 4 = 8 -14x = 8 Divide each side by '-14'. x = -0.5714285714 Simplifying x = -0.5714285714
| (7-x)(10-x)=(7)(10-1.5x) | | 6/10x=60 | | w/12.8=4 | | .40x+.15(140-x)=.19(140) | | -2(v+9)=7v+45 | | 6i+10y=-13 | | 2x-13=-7(x+7) | | 8x+4=-6+7x | | 3v=9/2 | | .25x+.15(140-x)=.19(140) | | y/4+3.2+5.2 | | 3v+6(v+2)=21 | | 13x=9x+12 | | 7(y-8)+2y=7 | | 30=6/5x | | -6u+3(u+7)=9 | | 3x-2-x=102 | | x(2x-5)+x(2x-2)=(4x+3)(x-2) | | .40x+.15(140-x)=.25(140) | | 2/3(4+3) | | 6x^4+5x^2-6=0 | | 3/8=v+6 | | (3x+4)*(3x+4)=144 | | 2q+6=5(a-3) | | 8.5x-6.96=38.08 | | 2(8x-7)=2(3+8x) | | y+1/5=-3/4 | | -0.09p-0.04(6-4p)=0.03(p-4)-0.12 | | 17x-4x+27=4x-18 | | y-1/2=-7/8 | | 8r-4r+4=7r-r | | -2x-1=-8 |